Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.2215/cjn.04761107
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Albuminuria and Total Proteinuria in Systemic Lupus Erythematosus Nephritis

Abstract: Background and objectives: Albuminuria is regarded a sensitive measure of progression of glomerular disease. This study was undertaken in patients who had systemic lupus erythematosus glomerulonephritis (n ‫؍‬ 57) and were followed in the Ohio SLE Study to determine whether measuring albuminuria offered clinical advantages over that of total proteinuria. Design, setting, participants, & measurements: Twenty-four-hour urine collections (n ‫؍‬ 127) were obtained at baseline and annually for measurement of microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…Studies have shown a signiWcant correlation between the depth of GFR decline and the amount of albumin in urine (Mojiminiyi et al 2000). The prime example of using albuminuria to monitor progression of early glomerular injury is in diabetic glomerulosclerosis (Birmingham et al 2008). The urinary microalbumin excretion was also used as a functional predictor of the glomerular Table 4 The correlation between Cr-exposed level and renal injury biomarkers in Cr exposed workers and control (Awad et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a signiWcant correlation between the depth of GFR decline and the amount of albumin in urine (Mojiminiyi et al 2000). The prime example of using albuminuria to monitor progression of early glomerular injury is in diabetic glomerulosclerosis (Birmingham et al 2008). The urinary microalbumin excretion was also used as a functional predictor of the glomerular Table 4 The correlation between Cr-exposed level and renal injury biomarkers in Cr exposed workers and control (Awad et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous reports on the use of random spot urine P/C ratio to estimate 24-hour proteinuria in non-SLE CKD [5, 6]. However, it cannot be assumed that the results of proteinuria testing in non-SLE CKD will be the same as that of SLE GN [22]. Relevant differences include that SLE GN patients are overwhelmingly female, and generally smaller than non-SLE CKD.…”
Section: Discussionmentioning
confidence: 99%
“…This results in lower urine creatinine excretion rates in the SLE cohorts. In addition, SLE GN patients are more likely to manifest inflammation, which lowers serum albumin by increasing catabolism [22]. Also, data from SLE mouse models suggest that the renal tubular catabolism of filtered proteins is less than that of non-SLE models of kidney disease [22].…”
Section: Discussionmentioning
confidence: 99%
“…The mean value of uACR was statistically significant higher in group I than group II and III. The use of uACR was also used by Birmingham et al (2008) were it was found that it is a better forecaster for proteinuric renal flare allowing early declaration of renal flare especially in 2.16 ± 1.522 4.4000 ± 2.607 0.014* RRI = renal resistive index; MBP = Mean blood pressure; eGFR = estimated glomerular filtration rate; ESR = Erythrocyte sedimentation rate; CRP = C-reactive protein; Serum C3 = Serum complement 3; Serum C4 = Serum complement 4; SLICCRAS = Systemic lupus international collaborating clinics renal activity score; SLEDAI = Systemic lupus erythematosus disease activity index.…”
Section: Discussionmentioning
confidence: 99%